Precision Estimates of AASHTO T 304, AASHTO T 96, and AASHTO T 11 and Investigation of the Effect of Manual and Mechanical Methods of Washing on Sieve Analysis of Aggregates - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Research Results Digest 389: Precision Estimates of AASHTO T 304, AASHTO T 96, and AASHTO T 11 and Investigation of the Effect of Manual and Mechanical Methods of Washing on Sieve Analysis of Aggregates updates precision estimates of American Association of State Highway and Transportation Officials (AASHTO) T 96, T 304, and T 11.The report also examines the significance of the difference between variability of percent passing No. 200 sieve of 300-g and 500-g fine aggregate samples measured according to AASHTO T 11.In addition, NCHRP RRD 389 evaluates the effect of manual versus mechanical washing, by comparing the results of sieve analysis of PSP samples, washed manually or mechanically prior to being tested according to AASHTO T 11, T 27, or T 30.The following appendixes are not included in the print or PDF version of the publication, but are available for download from the project page for NCHRP Project 10-87. The appendixes are titled as follows:* Appendix A: Proficiency Sample Data Sheets and Instructions* Appendix B: T 96 Coarse Aggregate Graphs* Appendix C: T 304 Fine Aggregate Graphs* Appendix D: T 11 Coarse and Fine Aggregate Graphs* Appendix F: Coarse Aggregate—Washing Method Tables and Graphs* Appendix G: Fine Aggregate—Washing Method Tables and Graphs* Appendix H: Hot Mix Asphalt Ignition Oven—Washing Method Tables and Graphs* Appendix I: Hot Mix Asphalt Solvent Extraction—Washing Method Tables and Graphs
Keywords: Transportation and Infrastructure

Measuring and Removing Dissolved Metals from Stormwater in Highly Urbanized Areas - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 767: Measuring and Removing Dissolved Metals from Stormwater in Highly Urbanized Areas presents prototype best management practices (BMPs) for the removal of dissolved metals in stormwater runoff.The report presents three conceptual configurations in detail: two vault system configurations for urban and rural settings, and an inlet scupper with media for bridge deck drainage systems.The report also includes standard protocols to accurately measure the levels of dissolved metals in stormwater. Practical guidance on the use of these protocols is provided in an appendix to the final report. The report is accompanied by an Excel spreadsheet on CD designed to assist in sizing the filter bed in the vaults and the bridge deck inlet scupper.The CD is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD from an ISO image are provided below.Help on Burning an .ISO CD ImageDownload the .ISO CD ImageCD Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Health Impact Assessment of Shale Gas Extraction: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Natural gas extraction from shale formations, which includes hydraulic fracturing, is increasingly in the news as the use of extraction technologies has expanded, rural communities have been transformed seemingly overnight, public awareness has increased, and regulations have been developed. The governmental public health system, which retains primary responsibility for health, was not an early participant in discussions about shale gas extraction; thus public health is lacking critical information about environmental health impacts of these technologies and is limited in its ability to address concerns raised by regulators at the federal and state levels, communities, and workers employed in the shale gas extraction industry. Health Impact Assessment of Shale Gas Extraction is the summary of a workshop convened in 2012 by the Institute of Medicine (IOM) Roundtable on Environmental Health Sciences, Research, and Medicine to discuss the human health impact of shale gas extraction through the lens of a health impact assessment. Eminent scientists, physicians, public health experts, and representatives from government agencies at federal and state levels, from nongovernment organizations, from the business sector, and from interest groups representing the interests of the citizens met to exchange ideas and to inform on hydraulic fracturing as a means of extraction of natural gas. This report examines the state of the science regarding shale gas extraction, the direct and indirect environmental health impacts of shale gas extraction, and the use of health impact assessment as a tool that can help decision makers identify the public health consequences of shale gas extraction.
Keywords: Health and Medicine

Estimating the Economic Impact of Air Cargo Operations at Airports, Part 1: User’s Guidebook and Part 2: Research Report - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Airport Cooperative Research Program (ACRP) Web-Only Document 20: Estimating the Economic Impact of Air Cargo Operations at Airports, Part 1: User’s Guidebook and Part 2: Research Report provides guidance and tools to practitioners who estimate the economic value of air cargo facilities and operations to their communities and regions.
Keywords: Transportation and Infrastructure

Responding to Oil Spills in the U.S. Arctic Marine Environment - Transportation Research Board; National Research Council (The National Academies Press, 2014)
U.S. Arctic waters north of the Bering Strait and west of the Canadian border encompass a vast area that is usually ice covered for much of the year, but is increasingly experiencing longer periods and larger areas of open water due to climate change. Sparsely inhabited with a wide variety of ecosystems found nowhere else, this region is vulnerable to damage from human activities. As oil and gas, shipping, and tourism activities increase, the possibilities of an oil spill also increase. How can we best prepare to respond to such an event in this challenging environment? Responding to Oil Spills in the U.S. Arctic Marine Environment reviews the current state of the science regarding oil spill response and environmental assessment in the Arctic region north of the Bering Strait, with emphasis on the potential impacts in U.S. waters. This report describes the unique ecosystems and environment of the Arctic and makes recommendations to provide an effective response effort in these challenging conditions. According to Responding to Oil Spills in the U.S. Arctic Marine Environment, a full range of proven oil spill response technologies is needed in order to minimize the impacts on people and sensitive ecosystems. This report identifies key oil spill research priorities, critical data and monitoring needs, mitigation strategies, and important operational and logistical issues. The Arctic acts as an integrating, regulating, and mediating component of the physical, atmospheric and cryospheric systems that govern life on Earth. Not only does the Arctic serve as regulator of many of the Earth's large-scale systems and processes, but it is also an area where choices made have substantial impact on life and choices everywhere on planet Earth. This report's recommendations will assist environmentalists, industry, state and local policymakers, and anyone interested in the future of this special region to preserve and protect it from damaging oil spills.
Keywords: Environment and Environmental Studies; Earth Sciences

Risks and Risk Governance in Shale Gas Development: Summary of Two Workshops - National Research Council (The National Academies Press, 2014)
Natural gas in deep shale formations, which can be developed by hydraulic fracturing and associated technologies (often collectively referred to as "fracking") is dramatically increasing production of natural gas in the United States, where significant gas deposits exist in formations that underlie many states. Major deposits of shale gas exist in many other countries as well. Proponents of shale gas development point to several kinds of benefits, for instance, to local economies and to national "energy independence". Shale gas development has also brought increasing expression of concerns about risks, including to human health, environmental quality, non-energy economic activities in shale regions, and community cohesion. Some of these potential risks are beginning to receive careful evaluation; others are not. Although the risks have not yet been fully characterized or all of them carefully analyzed, governments at all levels are making policy decisions, some of them hard to reverse, about shale gas development and/or how to manage the risks. Risks and Risk Governance in Shale Gas Development is the summary of two workshops convened in May and August 2013 by the National Research Council's Board on Environmental Change and Society to consider and assess claims about the levels and types of risk posed by shale gas development and about the adequacy of existing governance procedures. Participants from engineering, natural, and social scientific communities examined the range of risks and of social and decision-making issues in risk characterization and governance related to gas shale development. Central themes included risk governance in the context of (a) risks that emerge as shale gas development expands, and (b) incomplete or declining regulatory capacity in an era of budgetary stringency. This report summarizes the presentations on risk issues raised in the first workshop, the risk management and governance concepts presented at the second workshop, and the discussions at both workshops.
Keywords: Behavioral and Social Sciences; Energy and Energy Conservation; Environment and Environmental Studies

Thin Asphalt Concrete Overlays - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 464: Thin Asphalt Concrete Overlays documents the current state of the practice as well as research efforts on the use of thin asphalt concrete overlays for pavement maintenance, rehabilitation, and preservation.
Keywords: Transportation and Infrastructure

Backcountry Airstrip Preservation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Airport Cooperative Research Program (ACRP) Synthesis 55: Backcountry Airstrip Preservation catalogues the uses, benefits, and threats to backcountry airstrips and identifies practices and strategies to manage these threats.
Keywords: Transportation and Infrastructure

Strategies to Optimize Real Property Acquisition, Relocation Assistance, and Property Management Practices - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 771: Strategies to Optimize Real Property Acquisition, Relocation Assistance, and Property Management Practices provides improved, integrated real property procedures and business practices in the project development and delivery process. The report also provides suggestions to improve property management practices. The report is accompanied by a CD-ROM that contains an integrated model of the transportation project development and delivery process, including a real property acquisition and relocation assistance model and reference work schedule.The CD-ROM is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM ImageDownload the .ISO CD-ROM Image(Warning: This is a large file and may take some time to download using a high-speed connection.)CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Harvesting the Fruits of Inquiry: How Materials Discoveries Improve Our Lives (The National Academies Press, 2014)
The field of condensed matter and materials research has played a key role in meeting our nation's needs in a number of areas, including energy, health, and climate change. Harvesting the Fruits of Inquiry highlights a few of the societal benefits that have flowed from research in this field. This report communicates the role that condensed matter and materials research plays in addressing societal needs. The report uses examples to illustrate how research in this area has contributed directly to efforts to address the nation's needs in providing sustainable energy, meeting health needs, and addressing climate change issues. Written in an accessible style, this report will be of interest to academia, government agencies, and Congress.
Keywords: Engineering and Technology

Guide to Using Existing Pavement in Place and Achieving Long Life - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s second Strategic Highway Research Program (SHRP 2) Report S2-R23-RW-2: Guide to Using Existing Pavement in Place and Achieving Long Life provides guidance for selecting, designing, and constructing long-life pavements using existing pavement structure. The guide is intended to complement the design tools developed by SHRP 2 Report S2-R23-RR-1: Using Existing Pavement in Place and Achieving Long Life.This project also produced Addendum 1 and Addendum 2 to update and expand the information presented in the guide.
Keywords: Transportation and Infrastructure

State Bridge Load Posting Processes and Practices - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 453: State Bridge Load Posting Processes and Practices is a synthesis of the practices of U.S. state governments in restricting weights of vehicles that can cross highway bridges and culverts to levels below legal loads. Bridges and culverts restricted for vehicle weights are called load posted structures. The load posting practices of bridge owners include the identification of structures to post for load, the evaluation of safe load capacities of these structures, and the implementation of restrictions on vehicle weights at structures.
Keywords: Transportation and Infrastructure

Memorial Tributes: Volume 18 - National Academy of Engineering (The National Academies Press, 2014)
This is the 18th Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964. Under the charter of the National Academy of Sciences, the National Academy of Engineering was formed as a parallel organization of outstanding engineers. Members are elected on the basis of significant contributions to engineering theory and practice and to the literature of engineering or on the basis of demonstrated unusual accomplishments in the pioneering of new and developing fields of technology. The National Academies share a responsibility to advise the federal government on matters of science and technology. The expertise and credibility that the National Academy of Engineering brings to that task stem directly from the abilities, interests, and achievements of our members and foreign associates, our colleagues and friends, whose special gifts we remember in this book.
Keywords: Biography and Autobiography

Development of Unconventional Hydrocarbon Resources in the Appalachian Basin: Workshop Summary - National Research Council (The National Academies Press, 2014)
Development of Unconventional Hydrocarbon Resources in the Appalachian Basin is the summary of a workshop convened by the National Research Council to examine the geology and unconventional hydrocarbon resources of the Appalachian Basin; technical methods for producing unconventional hydrocarbons and disposing of wastewater; the potential effects of production on the environment; relevant policies and regulations; and priorities for future scientific and engineering research. Workshop presentations by experts in the fields of geosciences and engineering examined the numerous geoscientific aspects of hydrocarbon development from unconventional resources, including natural gas, oil, and natural gas liquids. Shale gas is the fastest growing source of U.S. natural gas. Most of the oil and gas produced in the United States comes from conventional reservoirs in which hydrocarbons have accumulated in discrete structural or stratigraphic traps below relatively impermeable rock and above a well-defined hydrocarbon-water interface. However, a growing fraction comes from unconventional reservoirs - geographically extensive accumulations of hydrocarbons held in low-permeability rock with diffuse boundaries and no obvious traps or hydrocarbon-water contacts. In the Appalachian Basin, shale gas development is proceeding in Ohio, Pennsylvania, and West Virginia, while New York and Maryland have commissioned studies to assess potential impacts. Development of Unconventional Hydrocarbon Resources in the Appalachian Basin focuses on the main hydrocarbon-bearing geologic formations in and around the Appalachian Basin, including the Marcellus, Utica, and Devonian shales, and their estimated resources, current production levels, and projected output. This report examines the potential effects on surface water and groundwater quality and quantity; potential effects on landscapes, including soil and living organisms, and other environmental systems; and technical and engineering processes for exploration and production.
Keywords: Earth Sciences

Opportunities to Use Remote Sensing in Understanding Permafrost and Related Ecological Characteristics: Report of a Workshop - National Research Council (The National Academies Press, 2014)
Permafrost is a thermal condition -- its formation, persistence and disappearance are highly dependent on climate. General circulation models predict that, for a doubling of atmospheric concentrations of carbon dioxide, mean annual air temperatures may rise up to several degrees over much of the Arctic. In the discontinuous permafrost region, where ground temperatures are within 1-2 degrees of thawing, permafrost will likely ultimately disappear as a result of ground thermal changes associated with global climate warming. Where ground ice contents are high, permafrost degradation will have associated physical impacts. Permafrost thaw stands to have wide-ranging impacts, such as the draining and drying of the tundra, erosion of riverbanks and coastline, and destabilization of infrastructure (roads, airports, buildings, etc.), and including potential implications for ecosystems and the carbon cycle in the high latitudes. Opportunities to Use Remote Sensing in Understanding Permafrost and Related Ecological Characteristics is the summary of a workshop convened by the National Research Council to explore opportunities for using remote sensing to advance our understanding of permafrost status and trends and the impacts of permafrost change, especially on ecosystems and the carbon cycle in the high latitudes. The workshop brought together experts from the remote sensing community with permafrost and ecosystem scientists. The workshop discussions articulated gaps in current understanding and potential opportunities to harness remote sensing techniques to better understand permafrost, permafrost change, and implications for ecosystems in permafrost areas. This report addresses questions such as how remote sensing might be used in innovative ways, how it might enhance our ability to document long-term trends, and whether it is possible to integrate remote sensing products with the ground-based observations and assimilate them into advanced Arctic system models. Additionally, the report considers the expectations of the quality and spatial and temporal resolution possible through such approaches, and the prototype sensors that are available that could be used for detailed ground calibration of permafrost/high latitude carbon cycle studies.
Keywords: Earth Sciences

Pilot Testing of the TCAPP Decision Guide and Related Capacity Products: Hoopstick Creek, South Carolina - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s second Strategic Highway Research Program (SHRP 2) Report S2-C39-A1 titled Pilot Testing of the TCAPP Decision Guide and Related Capacity Products: Hoopstick Creek, South Carolina evaluates and proposes enhancements to the Transportation for Communities—Advancing Projects through Partnerships (TCAPP) collaborative planning tool. TCAPP is now known as PlanWorks. The report explores the tool’s value in providing guidance to facilitate project partners to work collaboratively toward environmental permitting decisions for South Carolina Department of Transportation (SCDOT) projects.
Keywords: Transportation and Infrastructure

Continuing Project to Synthesize Information on Highway Problems: 2015 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Research Results Digest 392: Continuing Project to Synthesize Information on Highway Problems is a digest of the progress and status of NCHRP Project 20-5, “Synthesis of Information Related to Highway Problems.”
Keywords: Transportation and Infrastructure

Evaluation of the Moisture Susceptibility of WMA Technologies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 763: Evaluation of the Moisture Susceptibility of WMA Technologies presents proposed guidelines for identifying potential moisture susceptibility in warm mix asphalt (WMA). The report also suggests potential revisions to the Appendix to AASHTO R 35, “Special Mixture Design Considerations and Methods for WMA” as a means to implement the guidelines.
Keywords: Transportation and Infrastructure

Continuing Project to Synthesize Information on Highway Problems: 2014 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Research Results Digest 386: Continuing Project to Synthesize Information on Highway Problems is a digest of the progress and status of NCHRP Project 20-5, “Synthesis of Information Related to Highway Problems.”
Keywords: Transportation and Infrastructure

Innovations to Locate Stacked or Deep Utilities - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s second Strategic Highway Research Program (SHRP 2) Report S2-R01C-RW-1: Innovations to Locate Stacked or Deep Utilities documents research and tested tools that could be used to help locate buried utilities or utility systems in highway construction projects.SHRP 2 Renewal Projects R01B and R01C developed a report about the testing of the geophysical tools developed in the R01B and R01C projects.
Keywords: Transportation and Infrastructure